Behavior of Heterotrigona itama in Hydroponic Melon (Cucumis melo L.) Planting in Greenhouse with Insecticide Spraying - Seprido; Desta Andriani; Chairil Ezward; A. Haitami; Nariman Hadi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Sustaining and improving melon production is essential to fulfill the increasing demand for melon fruit in Indonesia. In order to maintain this level of production, it is necessary to utilize insecticides to manage the pests that pose a threat to melon crops. This research aims to assess the impact of insecticide application on the pollination activity of Heterotrigona itama, a vital pollinating insect for melon plants. This research aimed to investigate the effect of Heterotrigona itama activity on melon plants in a greenhouse treated with insecticides. The study was carried out utilizing a survey-based methodology. Data was collected on several aspects of Heterotrigona items' behavior before and after applying insecticides. The research findings demonstrated that using insecticides on melon crops within a controlled environment decreased the frequency of visits from Heterotrigona itama to the melon flowers. Additionally, it was observed that the application of insecticides resulted in the mortality of Heterotrigona itama within the initial six days following the insecticide spraying. On the second day, the maximum number of individuals present was 14. The analysis of Heterotrigona itama honey revealed that the detected levels of pesticide residues were lower than the benchmark dose response (BMR) threshold.